Digital Branding On Instagram For Educational Business: A Comparative Study Of Local Cram Schools In Sidoarjo (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to conduct comparative observations of the digital branding approaches of Instagram in an effort to study their ability to facilitate brand awareness. The research targets the official accounts of three Sidoarjo local cram schools' official pages: @qalbun.ilmiah, @bimbel.pakmuss, and @lkpbrilliant.09. The study employs a qualitative descriptive design with the help of content analysis and engagement rates in order to distinguish between differences in branding characteristics, visual identity consistency, type of content, frequency, and public interaction. Data were collected from official Instagram pages for a period of one month. The findings show that different digital branding strategies are employed by each institution. @qalbun.ilmiah emphasizes playful and engaging visual identity with robust layout to its organizational values of, @bimbel.pakmuss on achievement and motivational content, and @lkpbrilliant.09 on special campaigns and endorsements. Comparative analysis appears that strong branding consistency, excellent photos, and participative spotlights significantly assist in promoting increased audience activity and awareness. Research suggests that Instagram is a potentially effective vehicle through which local cram schools can establish brand situating, as methods are strategically designed to fit enlightening, brief, and naturally substance. These findings yield down-to-earth experiences for pedagogical teach in maximizing digital branding methods to raise awareness and competitiveness in the regional education market.
Keywords: digital branding; Instagram; brand awareness; cram school; Sidoarjo